Penegakan Hukum Label Halal Terhadap Peredaran Produk Makanan Kemasan Home Industry di Kota Binjai - Zahra Afiqah; Zulham (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study discusses the law enforcement of halal labels on packaged food products produced by home industries in Binjai City, in accordance with the provisions of Law Number 33 of 2014 concerning Halal Product Assurance. Packaged food products from home industries are increasingly circulating in the community, but not all have halal labels which are the rights of consumers, especially Muslim consumers. In Binjai City, there are still many home industry packaged food traders who do not apply halal labeling to their packaged food products, even though the Law requires products circulating and traded in the territory of Indonesia to be halal certified. This is a special concern considering the importance of halal labels in protecting the rights of Muslim consumers. This study aims to analyze the extent to which the implementation of halal label obligations is applied by home industry business actors, as well as the role of the government and related institutions in enforcing the law. The method used in this study is empirical juridical with a qualitative approach, through field studies and interviews with business actors, consumers, and authorities in Binjai City. The results of the study indicate that business actors' awareness of the importance of halal labels is still low, which is caused by limited information, certification costs, and lack of supervision from the authorities. Law enforcement is still not optimal, so cooperation is needed between local governments, the halal product guarantee organizing body (BPJPH), and other related agencies in providing education, facilitation, and ongoing supervision